PENGARUH PENDIDIKAN AGAMA ISLAM TERHADAP PEMBELAJARAN ANTIKORUPSI DI SMAN 6 KABUPATEN TANGERANG - Ahmad Aziz Faozi (STIT Islamic Village Tangerang, 2020)
This study aims to obtain empirical data on the Effects of Islamic Religious Education on Anti-Corruption Learning in SMA Negeri 6 Tangerang. The method used in this research is a quantitative descriptive method with the method of calculating the correlation study approach and is supported by the calculation of Statistical Product and Service Solutions (SPSS) version 21.0, in order to produce accurate data. In this study, the population was 116 students of SMA Negeri 6 Tangerang. Samples were taken as many as 30 students. By using random sampling techniques, the instrument used as a tool in data collection in the form of a behavior scale (Likert) to determine and measure Islamic Religious Education in a school scope. Data analysis uses the Product Moment and Statistical Product and Service Solutions (SPSS) formulas, which produce Rcounts greater than Rtable (0.564> 0.374), in this case Ho is rejected and Ha is accepted. And the coefficient of determination shows 31.36%. This means that the level of influence is sufficient or moderate. This study concludes that between variables X and Y there is a positive and significant effect between Islamic Religious Education in anti-corruption learning in SMA Negeri 6 Tangerang. So that it can be interpreted as the higher the score of Islamic Religious Education in schools, the score will be followed by anti-corruption on students.